General equilibrium, overlapping generations models, and optimal growth theory - Bewley Truman E (Cambridge Harvard Univ Press, 2007)
This book presents an original exposition of general equilibrium theory for advanced undergraduate and graduate-level students of economics. It contains detailed discussions of economic efficiency, competitive equilibrium, the first and second welfare th
Keywords: Econometric models; Economic development; Equilibrium(Economics); Mathematical models